Single Phase Rectifier with Soft Switching using Pattern Raspberry Pi - Adha, Mohamad Afiq; Zulkifli , Shamsul Aizam (Evolution in Electrical and Electronic Engineering, 2022)
This project uses the Raspberry Pi model 3 B+ microcontroller to control and build a single-phase rectifier output voltage for soft-switching pattern for Pulse Width Modulation (PWM). The algorithm used in Simulink MATLAB has been applied with the soft-switching outcome takes precedence. The Main feature of this project the Raspberry Pi Microcontroller is to control the whole system that allows to control gate signal of power switches. This project to aim by creating algorithm soft switching in PWM scheme from Simulink MATLAB a MOSFET semiconductor allows for soft- switching pattern in a full wave rectifier. There is one technique used in this project to achieve soft- switching patterns or known is Zero Voltage Switching (ZVS). To make sure to get the desired output voltage with PI controller is used in this system and functionally the output value is equal to the references value and also achieve a minimum error for PWM generation. This is a project to show a generation of soft switching using Rpi microcontroller and designing algorithm of Simulink MATLAB.